Catalogue of Construction Products with Recycled Content from Construction and Demolition Waste. (June 2019) - Pavlů, T; Pešta, J; Volf, M; Lupíšek, A
Abstract: The main objective of the present project for the Czech government was to create a catalogue of construction products and materials which contain recycled content from construction and demolition waste. The motivation for the work was to support a higher utilization of construction products with the content of secondary raw materials in the Czech Republic. It was designed for architects, designers, civil engineers, construction contractors and public and private investors. The catalogue provides an overview of products with recycled content, a list of valid requirements on the utilization of recycled materials listed in standards and legislation. Examples of good practice are presented to break the existing psychologic barriers to the use of secondary raw materials in the Czech construction industry. This contribution summarizes the findings in the field of the recycling of construction and demolition waste and its further use as produced secondary raw materials in the construction industry.